2007
DOI: 10.1073/pnas.0700004104
|View full text |Cite
|
Sign up to set email alerts
|

Molecular diagnosis of pituitary adenoma predisposition caused by aryl hydrocarbon receptor-interacting protein gene mutations

Abstract: Pituitary adenomas are common neoplasms of the anterior pituitary gland. Germ-line mutations in the aryl hydrocarbon receptor-interacting protein (AIP) gene cause pituitary adenoma predisposition (PAP), a recent discovery based on genetic studies in Northern Finland. In this population, a founder mutation explained a significant proportion of all acromegaly cases. Typically, PAP patients were of a young age at diagnosis but did not display a strong family history of pituitary adenomas. To evaluate the role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
155
4
10

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(180 citation statements)
references
References 38 publications
11
155
4
10
Order By: Relevance
“…Bold represents the more likely at-risk haplotype shared by at least two subjects. near 7% (7,8). This prevalence reaches 14.3% in patients with GH-secreting tumors diagnosed before 25 years old (28).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Bold represents the more likely at-risk haplotype shared by at least two subjects. near 7% (7,8). This prevalence reaches 14.3% in patients with GH-secreting tumors diagnosed before 25 years old (28).…”
Section: Discussionmentioning
confidence: 90%
“…In 2006, Vierimaa et al (4) identified mutations in the aryl hydrocarbon receptor interacting protein (AIP) gene in the familial setting of PA. In FIPA kindreds, AIP mutations occur in 15-20% of cases (5), whereas they occur at a very low frequency in sporadic cases, between 0 and 4% (6,7,8,9). Because patients mutated for AIP (AIPmut) have typically early onset disease and larger PA compared with controls (10), Tichomirowa et al (11) performed AIP screening in young patients with isolated sporadic macroadenomas and identified that nearly 12% of patients had germline AIP mutations.…”
Section: Introductionmentioning
confidence: 99%
“…From a cohort of 74 pediatric patients with isolated CD, one presented with AIP and two with MEN1 mutations (14). Altogether, mutations in MEN1, AIP, CDKN1B or CDKN2C (encoding p18/INK4C) are rarely found in patients with CD (14,15,19,20). These features point to evidence against inheritance caused by germline mutations and suggest an acquired genetic basis of CD.…”
Section: Genetic Events In CDmentioning
confidence: 96%
“…This suggests that amino acid substitutions, such as R16H for instance, could be expected to have functional significance. Indeed, since we reported germline R16H changes in a FIPA family, others have noted similar mutations in four sporadic pituitary adenoma patients and also in the germline and tumors of two patients with colorectal carcinoma (and family histories of colorectal, carcinoid, and other tumors) (47,48). A full appreciation of the effect of R16H on AIP expression and/or function will be required to determine whether this is Familial isolated pituitary adenomas truly a pathogenic mutation.…”
Section: The Genetics Of Fipamentioning
confidence: 99%
“…With the identification of AIP mutations as being involved in the etiology of familial pituitary tumors, the issue of screening has been raised (47). In particular, it has been suggested that immunohistochemistry for AIP in pituitary tumor tissue be used to screen operated patients for mutations.…”
Section: Perspectivesmentioning
confidence: 99%